PENINGKATAN HASIL BELAJAR IPA KELAS IV MELALUI MODEL COOPERATIVE LEARNING TIPE MAKE - A MATCH DI SDN 060830 MEDAN PETISAH - Sinaga, Lasmaria Agnes; Sitanggang, Manisha; Pandiangan, Christine Joice; Marpaung, Dwi Feby Aprillita; Sitorus, Bella Dame Octavia (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
prompted this study. Identified issues included students' difficulty in understanding weather and climate topics, low classroom participation, and teacher-centered instructional methods. This research aims to improve student learning outcomes through the application of the Cooperative Learning model, specifically the Make-A-Match type. The study employed Classroom Action Research (CAR), carried out over two cycles. The findings indicate a significant improvement in student achievement, with the average score increasing from 75.4 in the first cycle to 89 in the second cycle. Furthermore, student motivation and classroom engagement improved, with most students categorized as “Developing” to “Proficient”. In conclusion, the Make-A-Match model effectively enhances science learning outcomes and serves as an engaging, collaborative, and active learning approach suitable for primary school education.